2002
DOI: 10.1038/sj.bjc.660502
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of somatic mutations in the FH/multiple cutaneous leiomyomatosis gene in sporadic leiomyosarcomas and uterine leiomyomas

Abstract: Germline mutations in the fumarate hydratase gene at 1q43 predispose to dominantly inherited skin and uterine leiomyomata and leiomyosarcomas. The enzyme, which is a component of the tricarboxylic acid cycle, acts as a tumour suppressor. To evaluate fumarate hydratase in respective sporadic tumours, we analysed a series of 26 leiomyosarcomas and 129 uterine leiomyomas (from 21 patients) for somatic mutations in fumarate hydratase and allelic imbalance around 1q43. None of the 26 leiomyosarcomas harboured somat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 12 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Three of these credible cases occurred in Finnish HLRCC patients 31,32(p12), and 2 were identified by homozygous FH deletion in a molecular study without immunohistochemical or clinicopathologic correlation 33. We identified 305 reported cases of uLMS studied by FH IHC, none of which were found to be FHd 2–4,6,21,34–36. And of 197 uLMS examined for FH deficiency by molecular testing 33–37, only 2 had molecular alterations consistent with FH inactivation, both of which stemmed from a single study of just 8 uLMS 33.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these credible cases occurred in Finnish HLRCC patients 31,32(p12), and 2 were identified by homozygous FH deletion in a molecular study without immunohistochemical or clinicopathologic correlation 33. We identified 305 reported cases of uLMS studied by FH IHC, none of which were found to be FHd 2–4,6,21,34–36. And of 197 uLMS examined for FH deficiency by molecular testing 33–37, only 2 had molecular alterations consistent with FH inactivation, both of which stemmed from a single study of just 8 uLMS 33.…”
mentioning
confidence: 99%
“…We identified 305 reported cases of uLMS studied by FH IHC, none of which were found to be FHd 2–4,6,21,34–36. And of 197 uLMS examined for FH deficiency by molecular testing 33–37, only 2 had molecular alterations consistent with FH inactivation, both of which stemmed from a single study of just 8 uLMS 33. Available data, though limited, likewise suggests that prospective morphologic screening for FHd uLMS is likely low-yield, if not entirely unfeasible 4,37.…”
mentioning
confidence: 99%
“…Multiple studies have also reported an association between FH gene mutations and the development of sporadic tumors, therefore it has been hypothesized that it functions as a tumor suppressor gene [5,17]. However, this is still a controversial issue as subsequent research did not confirm the role of FH gene defects in sporadic tumorigenesis [18,19].…”
Section: Figure 5 -(A-d) Immunohistochemical Staining Showing Diffuse Positivity For Actin (A ×50) and Vimentin (B ×50) Positivity For CDmentioning
confidence: 99%